The first two decisions of the European Court of Justice on the law applicable to employment contracts - Gulotta, Carla (CUADERNOS DE DERECHO TRANSNACIONAL, 2013)
Abstract: The article examines the first two decisions of the Court of Justice of the EuropeanUnion on Article 6 of the Rome Convention on the law applicable to employment contracts.The author underlines the effort of the Court in giving raise to a well integrated European systemof conflict of laws and international procedure’s rules. Building on the value given by the Court to itsprevious case law on grounds for jurisdiction in employment contracts, the author then argues that sucha system is thoroughly oriented towards a substantive (not formal) construction of conflict of laws’rules,in view of attaining the aim of protection of the employee. Key words: Rome Convention on the law applicable to contractual obligation, notion of «habitualplace of work», employees performing their work in more than one State. Estratto: Il contributo esamina le prime due sentenze nelle quali la Corte di giustizia dell’Unioneeuropea interpreta l’art. 6 della Convenzione di Roma, relativo alla legge applicabile ai contratti individualidi lavoro. L’autore sottolinea lo sforzo della Corte nella ricostruzione di un sistema di dirittointernazionale privato e processuale europeo organico e ben integrato. Sulla scorta del valore attribuitodalla Corte alla propria precedente giurisprudenza sui titoli di giurisdizione in materia di contratto dilavoro, l’autore sostiene che tale sistema appare fortemente orientato verso un’interpretazione materiale(non formale) delle regole di conflitto, volta alla realizzazione della miglior tutela del lavoratore. Parole chiave: Convenzione di Roma sulla legge applicabile alle obbligazioni contrattuali,nozione di «luogo abituale di lavoro», dipendenti che prestano l’attività lavorativa in più di un Paese.